2003
DOI: 10.1113/eph8802606
|View full text |Cite
|
Sign up to set email alerts
|

Cardioventilatory Coupling in Resting Human Subjects

Abstract: In 48 conscious resting subjects we examined the temporal coupling of heart beat timing and the onset of inspiration (cardioventilatory coupling), and the relationship between coupling and spectral indices of autonomic function. Using the proportional Shannon entropy (SHα) of the RI‐1 interval (interval between inspiration and the preceding ECG R wave) as a measure of coupling we detected statistically significant coupling in 32 of the 48 subjects. This was confirmed by visual inspection of time series plots o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 33 publications
6
81
0
Order By: Relevance
“…breathing frequency [45] similar to that found in slow pranayama. Cardioventilatory coupling, found during deep breathing exercises, indicates a synchronization mechanism that coordinates neural and non-neural activity.…”
Section: Hypothesissupporting
confidence: 70%
“…breathing frequency [45] similar to that found in slow pranayama. Cardioventilatory coupling, found during deep breathing exercises, indicates a synchronization mechanism that coordinates neural and non-neural activity.…”
Section: Hypothesissupporting
confidence: 70%
“…It is well known [23][24][25][45][46][47][48]51,52 that the phase of respiration influences the peripheral autonomic nervous system's outflow to the heart. However, till now it has never been shown when exactly this happens inside the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Description of cardiorespiratory interaction in terms of coupling functions yields a new technique for the quantification of respiratory-related HRV. HRV is one of the central tools of psychophysiology and behavioural medicine 44 , and the respiratory component is a significant part of it [23][24][25][45][46][47][48] , representing mainly the vagal or parasympathetic part of the autonomic nervous system influences. Having introduced the time-continuous phase of the ECG, we obtain a continuous description of the HRV via the instantaneous frequency _ j e ðtÞ, instead of the commonly used discontinuous beat-to-beat description.…”
Section: Es Ps Eps Egmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Cardioventilatory coupling (CVC) is another concept, which specifically refers to the influence of timing of breathing on cardiac activity. 17,19,47 CVC is quantified based on the temporary alignment between the R waves of the electrocardiogram (ECG) and inspiratory onsets, using the R-peak to inspiratory-onset interval plot. Galletly and Larsen showed that during anesthesia CVC places the heart beats and inspiratory onsets such that they are maximally affected by vagal modulation of RSA implying common physiological roles and significant relationship between CVC and RSA.…”
Section: Introductionmentioning
confidence: 99%